Structural and morphological properties of titanium dioxide nanoparticles dopped by Boron atoms - Mironyuk, Ivan; Mykytyn, Igor; Vasylyeva, Hanna (Physics and Chemistry of Solid State, 2022)
The phase composition and morphology of boron-containing TiO2 nanoparticles obtained by the sol-gel method were investigated. The solution of titanium aqua complex [Ti (OH2)6]3+‧3Cl- was used as a precursor. Borate acid Н3ВО3 (promoter of the formation of rutile) was used as a modified reagent. A single-phase rutile TiO2 was obtained at a concentration of borate acid in the reaction mixture, which causes the formation of a 0.5В-TiO2 sample. The particles of 0.5В-TiO2 samples were in the villi-form, with a diameter of 0.8-1.2 nm, and a length of 16-24 nm. With an increase of the Н3ВО3 concentration in the reaction mixture, synthesized oxide materials (samples of 1.0В-TiO2 and 1.5В-TiO2) contain 70 % and 57% of anatase respectively, in addition to rutile phase. Titanium-borate monodentate molecules Ti(OH)3OB(OH)2‧2Н2О were formed during the synthesis of the 0.5B-TiO2 rutile sample. The interatomic distance of Ti-O in these particles is commensurate with the average length of the Ti-O – bond of TiO6 rutile octahedra. During the polycondensation process, the distance of the Ti-O molecule-promoter was reproduced as a pattern in the following octahedra of rutile crystals. Two types of titanium-borate molecules are formed in the reaction medium, during the synthesis of 1.0В-TiO2 and 1.5В-TiO2 samples. Molecules with a bidentate mononuclear structure Ті(ОН)2О2ВОН‧2Н2О in which the interatomic distance of Ti-O is commensurate with the average length of the Ti-O –bond in the anatase octahedra was formed. Therefore, titanium-borate molecules of the second type act as a promoter of the formation of the TiO2 anatase phase.